Da república social à ditadura bonapartista: a crítica da política em O 18 de brumário de Luís Bonaparte - Musetti, Felipe Ramos (2014)
This dissertation investigates the way Karl Marx develops the relationship between political revolution and social revolution, in the 18th Brumaire of Louis Bonaparte, seeking to highlight the importance of historical rise and decadence of the bourgeoisie to the elucidation of the limits of politics. Intends to seize the internal nexus of studied written, explaining the genesis of the categorial complex that integrates the physiognomy of the Marxian reflection. Thus, the first two chapters of the dissertation are dedicated to analytical understanding of the formative period of Marx's thought, which outlines the new ontological position achieved by the author through the critics of politics, speculative philosophy and political economy. Highlighting the main aspects of Marxian analysis of social being, the third chapter seeks to demonstrate the way in which The 18th Brumaire of Louis Bonaparte enriches Marx s critics of politics, when addressing the loss of illusions around the bourgeois Republic and the movement in which the State completes its process of constitution, assuming the Bonapartist form. It is shown how the investigated text makes explicit the indissoluble link between civil society and political State, both finding in capital the common denominator and structuring principle. The dissertation, therefore, turns to the negative conception Marx s work, seeking to observe the role of the modern State in managing the order of capital and conserving the bourgeois ideology